2021
DOI: 10.1002/jia2.25676
|View full text |Cite
|
Sign up to set email alerts
|

Examining healthcare transition experiences among youth living with HIV in Atlanta, Georgia, USA: a longitudinal qualitative study

Abstract: Introduction Virtually all youth living with HIV in paediatric/adolescent care must eventually transition to adult‐oriented HIV care settings. To date, there is limited evidence examining the perspectives of youth living with HIV longitudinally through the healthcare transition process. The objective of our study was to examine attitudes and experiences of youth living with HIV regarding healthcare transition, including potential change in attitudes and experiences over time. Methods We conducted a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…3 One US-based qualitative studies identified that AYHIV who prepared for readiness in transition program as a key factor in successful of transition, however, we did not find that AYHIV who participated in Happy Teen Program had a better outcome. 16 Our study suggests that virologically suppressed adolescents are likely to remain suppressed after transition to adult care, while those with virologic failure at the pediatric clinic were unlikely to suppress after transition. In contrast, we did find a small number of AYHIV developed virologic failure after transition despite a history of remaining suppressed in pediatric clinic.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…3 One US-based qualitative studies identified that AYHIV who prepared for readiness in transition program as a key factor in successful of transition, however, we did not find that AYHIV who participated in Happy Teen Program had a better outcome. 16 Our study suggests that virologically suppressed adolescents are likely to remain suppressed after transition to adult care, while those with virologic failure at the pediatric clinic were unlikely to suppress after transition. In contrast, we did find a small number of AYHIV developed virologic failure after transition despite a history of remaining suppressed in pediatric clinic.…”
Section: Discussionmentioning
confidence: 67%
“…3 One US-based qualitative studies identified that AYHIV who prepared for readiness in transition program as a key factor in successful of transition, however, we did not find that AYHIV who participated in Happy Teen Program had a better outcome. 16…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is derived from a mixed-methods prospective, observational cohort study evaluating healthcare transition among youth at a large HIV care center in Atlanta, Georgia, US [21][22][23]. Between August 2016 and June 2018, 70 participants were recruited from the pediatric clinic within 3 months prior to anticipated healthcare transition to adult care.…”
Section: Parent Studymentioning
confidence: 99%